The Effect of Health Promotion on Helminthic Infection Among the Garbage Collectors at the Final Disposal Site of Piyungan, Bantul, Yogyakarta - Resmiaini Resmiaini; Windadari Murni Hartini; Sri Sumarni (Pusat Kedokteran Tropis, 2012)
ABSTRACTIntroduction: Garbage collector is a group of workers with a high risk of developing helminthic infection. This is because the profession mostly related with garbage is susceptible to higher risk of exposure to worm egg. Health promotion for the use of self-protective equipments and personal hygiene is one of the ways of developing awareness among the garbage collectors to behave and act based on their knowledge. This would eventually reduce the incidence of helminthic.Objectives: To find out the effect of health promotion for the use of Self-Protective Equipment and personal hygiene in improving knowledge, attitude, and garbage collecting practice and to get a description on the helminthic infection.Methods: A quasi experiment study was conducted with Pretest and Posttest Group Design. Samples of the study were garbage collectors, who were selected with purposive sampling technique. The samples were divided into two groups: treatment group (25 respondents) and control group (25 respondents). Data were collected using questionnaires for knowledge, attitude, practice, and fecal samples. The data were analyzed using statistical analyses, namely, paired t-test and independent t-test with a significance level of p=0,05.Results: Knowledge who received health promotion (treatment group), on the helminthic infection was better than those in the control group, who did not receive health promotion. No significant difference was found for attitude and personal hygiene practice between the treatment group and the control group. A decrease of helminthic infection was found after the health promotion in both the treatment group and the control group.Conclusion: Health promotion can enhance the garbage collectors’ knowledge on the prevention and reduce the incidence of helminthic infections. Keywords: Health promotion, garbage collectors, helminthic infection